Trade strategy towards the third world - Helga Steeg (Intereconomics, 1973)
It is of paramount importance to expand the trade of less developed countries (LDCs). The Federal Government of Germany, being fully aware of this vital need, has created a number of effective instruments designed specifically to promote imports from these countries. The policy underlying all these measures is one of progressively liberallsing foreign trade by the removal of barriers obstructing that trade.
Keywords: 330; Germany